Genetic diversity in cowpea as revealed by random amplified polymorphic DNA - Mignouna, Hodeba D.; Ng, N.Q.; Ikea, J.; Thottappilly, G. (1998)
Knowledge of the genetic relationships and variability among cultivated germplasm is important for facilitating the transfer of useful genes and maximizing the use of available germplasm resources. In this study, random amplified polymorphic DNA (RAPD) markers were used to assess genetic diversity in cowpea (Vigna unguiculata (L). Walp) germplasm. Ninety-five accessions of three cultivar groups from diverse geographical origin across Africa, America and Asia were selected. One hundred and twenty random decamer primers were screened on four accessions, to assess their ability to detect polymorphisms in cowpea and nine of them were used in this study. RAPD fingerprinting patterns were analysed, and amplified polymorphic DNA bands used to construct a dendrogram based on the unweighed pair-group method using arithmetic averages (UPGMA). A high degree of genetic diversity was found among the cowpea accessions in our present study. This shows that RAPD markers are useful tools with which to study the genetic structure and enhance management of cowpea germplasm.